SYNTHESIS OF NANOCONTAINERS BASED ON MOLYBDENUM (Mo²⁺) CATION AND THE FLAVONOID QUERCITENE (Universal International Scientific Journal, 2026)
In this work, the synthesis of nanocontainers based on quercetin, a representative ofthe flavonoid class, and molybdenum(II) cations was investigated. The synthesis process was carriedout in a solution medium under alkaline conditions, resulting in the formation of coordinationnanostructures via a self-assembly mechanism. The obtained nanocontainers are characterized by highstability and functional properties and are considered promising for applications in catalysis and otherapplied fields
Keywords: Quercetin; Flavonoids; Molybdenum(II) cation